Understanding Chinese Consumers’ Livestreaming Impulsive Buying: An Stimulus-Organism-Response Perspective and the Mediating Role of Emotions and Zhong Yong Tendency - Gao, Hongli; Chen, Xinzhi; Gao, Hongling; Yu, Bin (Frontiers in Psychology, 2022)
We built a livestreaming impulsive buying model based on stimulus-organism-response (SOR) theory, and we explored the impact of atmospheric cues (ACELS) and sales promotion (SPELS) on impulsive buying (IBI) based on emotions (EOC) and Zhong Yong tendency (ZYT) of online consumers. Combined with holistic orientation, perspective integration, and harmony maintenance, ZYT is a cognitive process involving individual events. We gathered 478 samples using a questionnaire to test the proposed research model. The empirical findings show that as the stimuli in the livestreaming environment, ACELS and SPELS during livestreaming greatly boost EOC while significantly constraining consumers’ ZYT. Among online consumers, positive EOC promotes IBI, whereas ZYT dampens it. In addition, EOC and ZYT mediate the relationship between stimulus factors and response factors in parallel, resulting in four model mediation paths. By incorporating the SOR model, this study provides theoretical underpinnings for the role of cognitive processing in impulsive purchases, as well as useful guidance for e-commerce platforms and streamers to effectively understand Chinese consumers’ purchase behavior, which benefits the development of effective promotion strategies and the creation of powerful marketing tools.